Komunikasi Bencana Berbasis IoT: Analisis Pesan dan Literasi Digital SITABAH Sumedang - Yunita Sari; Dian Gustina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the content of SITABAH messages, measure community digital literacy, and develop and conduct a limited trial of adaptive message prototypes to improve disaster communication effectiveness. A mixed-methods approach was applied, consisting of content analysis of 10 SITABAH messages from disaster events in January 2024, a digital literacy survey of 150 respondents across six sub-districts, in-depth interviews with system managers and community members, and a prototype trial with 50 respondents. Data were analyzed using descriptive quantitative and thematic qualitative techniques with triangulation. The findings indicate that SITABAH has not functioned optimally as an early warning system: no messages contained early warnings, most focused on victims and damage, instructions were general, and no visual elements were used. The digital literacy survey revealed relatively high levels of information access (64–80%), but lower levels of message comprehension (56–72%) and readiness to act (48–60%). Prototype trials demonstrated that visual and interactive formats were clearer and more effective in encouraging readiness to act compared to standard text. The study concludes that SITABAH’s effectiveness can be enhanced through the integration of early warning features, adaptive message design, improved digital literacy, and the development of a multi-channel SITABAH.